An evaluation framework for land readjustment practices - Yilmaz, Ahmet; Cagdas, Volkan; Demir, Hulya (ELSEVIER SCI LTD, 2015)
Land readjustment (LR) is an important technique used in a variety of countries to realize the development plans by converting rural land into urban land and providing city infrastructure. Although the main aim and the processes are similar around the world, each country has a different degree of success in the application of LR, which reveals the need for a comprehensive evaluation. However, the research to date has generally tended to focus on describing the main concepts such as the usage, principles, advantages, and disadvantages of the existing implementations rather than evaluating LR. A systematic approach, which provides an objective basis and removes subjectivity by identifying good practices and their indicators, is needed to assess the strengths and weaknesses of the LR process. In this article, we analyzed a wide range of ISI journal articles on LR to establish a framework and a methodology that will help evaluate and compare the national LR processes. The main contribution of this article is to build an awareness for the establishment of an internationally agreed methodology to evaluate the performance of a country's LR in a systematical way, which is currently not available in the literature. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Land readjustment; Evaluation framework; Monitoring and evaluation; Performance indicators; EFFICIENT APPLICABILITY; URBAN TRANSFORMATION; EXPERIENCES; TOOL; Environmental Sciences & Ecology